The Application of Dynamic Zakat Percentage by Yusuf al-Qaradawy on the Professional Zakat in Indonesian BAZNAS - Haris, Gusnam (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2020)
Abstract: This article explores the comparison of professional zakat acquisition at BAZNAS Indonesia between the zakat acquisition using a standard percentage and using the dynamic percentage offered by Yusuf Al-Qaradawi. Currently, professional and mal zakat at BAZNAS Indonesia has provided the largest income of all existing zakat acquisition. The percentage of professional zakat is using standard percentage, 2,5% of someone professional income. With using the payroll system, all muzakkys have the same amount of zakat, no matter how much they earn. It is not fair to those who have a small income. Can the application of a dynamic percentage of zakat on professional zakat increase the zakat acquisition and fulfil the justice? It is based on professional zakat data obtained from the National UPZ Collection Division of BAZNAS, and the data is simulated using dynamic percentages. The result shows that the dynamic zakat percentage is more fulfilling legal justice than the standard percentage and the zakat acquisition—that application of the dynamic zakat percentage-- has increased by 16.9% compared to the application of the standard percentage that used by BAZNAS today. Abstrak: Artikel ini memaparkan perbandingan perolehan zakat profesi di BAZNAS Indonesia antara perolehan zakat menggunakan persentase tetap dengan perolehan zakat menggunakan persentase dinamis yang ditawarkan oleh Yusuf al-Qaradawi. Zakat mal dan profesi di BAZNAS Indonesia saat ini telah memberikan income terbesar dari keseluruhan perolehan zakat yang ada. Persentase zakat profesi yang digunakan adalah persentase tetap yaitu 2,5% dari pendapatan profesi seseorang. Melalui  sistem payroll, seluruh muzakky disamakan tanpa memandang besar kecilnya penghasilan mereka. Hal ini dipandang tidak adil bagi mereka yang berpenghasilan kecil. Mampukah penerapan persentase zakat dinamis atas zakat profesi lebih mendatangkan keadilan dan dapat meningkatkan perolehan zakat profesi? Data yang digunakan adalah data zakat profesi yang diperoleh dari Divisi Pengumpulan UPZ Nasional BAZNAS yang menggunakan persentase tetap, kemudian data tersebut disimulasikan dengan menggunakan persentase dinamis. Hasilnya menunjukkan bahwa penerapan persentase zakat dinamis lebih memenuhi keadilan hukum dibandingkan presentase zakat tetap. Selain itu, pengumpulan dana zakat dengan menggunakan persentase zakat dinamis mengalami peningkatan sebesar 16,9% dibandingkan penerapan persentase tetap yang digunakan oleh BAZNAS saat ini.